Disputed dams: Mapping the divergent stakeholder perspectives, expectations, and concerns over hydropower development in Iceland and Switzerland. (February 2021) - Voegeli, Guillaume; Finger, David C.
Highlights: Causal diagrams (CD) expose the full sequences of expected hydropower impacts. CD's detail scale can be adapted, enabling either in-depth or comparative analysis. Complexity of stakeholder views are incoherent with simplistic pro-/anti-dam groups. Conflicting views and uncertainty were reported on tangible and predictable aspects. Due to anticipation, socio-economic impacts can already occur at the planning stage. Abstract: The evaluation of the stakeholders' perception of new hydropower projects is essential for assessing public acceptance, ensuring local involvement, and identifying feasible and desirable changes towards sustainable development. This study uses the concept of causal diagrams (CD) to identify the individual perspectives of stakeholders of two new hydropower projects, one in Switzerland (Val d'Ambra project) and one in Iceland (Hvammvirkjun project). For this purpose, semi-structured interviews with relevant stakeholders were conducted, which were then categorized into 5 interest groups. Using the software Atlas.ti, we identified and sequenced the perceived causality of impact pathways of the two projects. The results are exposed in two series of 10 topical causal networks, and two aggregated diagrams. For each case, CDs expose the complexity of multi-sequenced causalities between elements of a very heterogeneous nature, as expected and reported by stakeholders. This approach enables the identification of inter- and intra-group conflicting perspectives, and perceived uncertainties, concerning both subjectives matters along with much more tangible and predictable aspects. Our method enables the identification of areas where further research or better transfer of information between stakeholders is required. It also exposes how hydropower impacts can differ in time and space, when in one case study, intracommunity tensions and conflicts were identified at the earliest project stage, along with psychological distress of some local residents. Based on the presented CD, we conclude that this method can facilitate communication and problem-solving in complex social-environmental situations amid multiple stakeholder categories, which heterogeneity should not be underestimated.